Analisis Anggaran Sebagai Alat Perencanaan Biaya Produksi Pada Cv Konveksi Mimo Di Kota Yogyakarta - Firmansyah, Firmansyah; Nurdiansyah, Dian Hakip (Jurnal Ilmiah Wahana Pendidikan, 2026)
This study aims to determine and analyze the production cost budget that has been prepared as a planning and control tool. The type of research is descriptive research with a survey approach, namely in the form of interviews related to budget reports at the CV Mimo convention and the type of data is primary data. Based on the research shows that at CV Mimo the budget preparation report is made as simple as possible. The results of the study that the budget at CV Mimo and sales have increased by 10% every year, this increase occurs due to the quality of good products.